FUNCTIONAL MODELING OF THE PROCESS OF CHOOSING THE BEST AVAILABLE TECHNIQUE - K. I. Erusheva (Тонкие химические технологии, 2017)
Due to the relevance of the problem of implementation of the Best Available Techniques (BAT) in the chemical industry of the Russian Federation it is necessary to develop a scientifically defensible transition process to BAT for chemical manufactures. For this purpose, the functional modeling methodology was used in the graphical notation IDEF0 standardized in the Russian Federation. The production process for the transition of a chemical manufacture to BAT was described as a hierarchical structure represented as a diagram consisting of functional blocks and arcs that connect them. First, the simulation object was represented as a single block with boundary arrows, which show how the simulated process is related to the environment. Then it was sequentially decomposed into diagrams of a lower level, i.e., stepwise hierarchical decomposition of the top-level context diagram was performed, which resulted in a set of interrelated diagrams that describe the processes and relationships between them and the environment. This allows us to clearly establish the order of actions that are performed at each stage of the transfer of chemical manufacture to BAT.